Obravnava skladnje pri pouku slovenščine v tretjem triletju osnovne šole, v gimnaziji ter srednjem strokovnem in poklicnem izobraževanju - Smolej, Mojca; Lampret, Nika (Slavia Centralis, 2020)
Teaching syntax in Slovene lessons in the third educational period of elementary school, gymnasium, and secondary technical and vocational educationsThe article presents a shortened and simplified overview of the results of the analysis regarding teaching Slovene syntax in elementary and secondary school. A review of printed learning material showed that most autonomous workbooks for teaching Slovene do not encourage elementary and high school pupils to reflect on the importance of the acquired knowledge in the field of syntax. In the examined autonomous workbooks, it is hardly possible to detect critical reflection and understanding of acquired knowledge.
Keywords: syntax; Slovene lessons; elementary schoo; elementary school; gymnasium; secondary; technical and vocational educations